Competitiveness versus demotivation in online learning: A phenomenological study among Indonesian University students - Tsania Rahmatilla (Jurnal Penelitian Ilmu Pendidikan, 2024)
The COVID-19 pandemic forced universities worldwide to adopt Learning Management Systems (LMS) for remote instruction, raising concerns about student motivation and engagement in online environments. This qualitative phenomenological study explores university students' lived experiences using LMS and how this environment influenced their learning motivation. Seven undergraduate students from a public university in Indonesia were purposively selected. Data were collected through in-depth interviews, focus group discussions (FGD), and document review (LMS screenshots), then analyzed thematically. Two major themes emerged. Theme 1, Demotivation versus Competitiveness: Some students reported decreased responsibility and motivation, experiencing procrastination and boredom. Conversely, other students experienced increased competitive drive, setting personal task targets and enjoying the privacy of task completion. Theme 2, Flexibility: Students universally valued the temporal and spatial flexibility of LMS, although this required greater self-regulation. LMS-based online learning elicited contrasting student responses. While it enhanced competitiveness for some students, it reduced motivation for others. Active instructor engagement in fostering learner autonomy and providing support is essential to maximize LMS advantages without compromising student engagement. These findings highlight the need for balanced instructional design that combines technology affordances with meaningful human interaction.